A Clinical and Psychopathological Approach to Radicalization Among Adolescents - Campelo, Nicolas; Oppetit, Alice; Thompson, Caroline; Cohen, David; Louet, Estelle (Frontiers in Psychiatry, 2022)
Recent studies have shown higher rates of radicalisation of adolescents than in the 2000s. Since 2015, radicalisation prevention units have been implemented in child and adolescent psychiatry departments in France. We aimed to report on the psychopathology of adolescents who were followed up in a university department due to their ‘radical conduct’. Based on the available clinical data (from child psychiatry consultations, long-term family and/or individual therapy, and psychological testing) for 20 adolescents with ‘radical conduct’, we examined the nature of their radical conduct, their psychopathology, their family characteristics, and the existence or absence of traumatic experiences. Among the 20 adolescents, 4 had radical conduct associated with a delusional syndrome (schizophrenia or a psychotic episode after substance abuse). For the other 16, we found no psychotic conditions. The analysis of other data showed that the adolescents shared some characteristics, such as an important prevalence of intrafamilial violence, sexual abuse, imprisonment of family members, traumatic family histories, and significant psychological control or dependence phenomena occurring in divided families. This diversity of psychopathologies appears consistent with previous studies highlighting the relevance of diverse profiles depending on the presence of a delusional syndrome, the individual’s gender and the individual’s attraction to violence. Finally, we discuss some psychopathological hypotheses and make therapeutic recommendations. We believe that child and adolescent psychotherapy/psychiatry has a role to play in countering violent extremism by offering adolescents a way out of radical commitment.